2015
DOI: 10.4081/ijfs.2015.5499
|View full text |Cite
|
Sign up to set email alerts
|

Activity of R(+) limonene against Anisakis larvae

Abstract: The aim of this work is to evaluate the activity of R(+) limonene of against Anisakidae larvae. Its effectiveness was tested in vitro. The results obtained showed a significant activity of the compound against Anisakis larvae, suggesting further investigation on its potential use in the industrial marinating process. In this regard, the use of R(+) limonene in seafood products could be interesting, also due the sensory attributes resulting from its use and its relatively safe status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Camphene is known for its activity against fungi and plant nematodes; no data have been reported for Anisakis . Anisakicidal activity of Limonene is instead reported by several authors as pure compound and as major constituent of several essential oil…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Camphene is known for its activity against fungi and plant nematodes; no data have been reported for Anisakis . Anisakicidal activity of Limonene is instead reported by several authors as pure compound and as major constituent of several essential oil…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless, the volatile profile of ginger essential oil displayed some differences in the chemical composition, especially for limonene, which was not present and was replaced by β ‐phellandrene (Table ). Limonene's efficacy against Anisakis larvae is well known, and camphene has been reported as an antifungal and antitumor compound, and recently as an anisakicidal agent . Finally, 1,8‐cineole (66.0%), linalool (9.7%), β ‐pinene (9.7%), and α ‐pinene (6.9%) were the major compounds of the volatile fraction of olive oil flavored with laurel.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, essential oils (EOs), aromatic oily liquids obtained from plant materials, are well known for their preservative properties. These substances and their components are used in food, pharmaceutical and cosmetic industries, for their antibacterial, antifungal, antiviral, nematocidal, anti-carcinogenic and antioxidant properties (Frassinetti et al , 2011; Giarratana et al , 2014, 2015a, 2015b; Rota et al , 2008; Silva-Angulo et al , 2015). Bergamot essential oil (BEO), extracted from the peel of Citrus bergamia Risso , is characterized by several of these properties (Navarra et al , 2016; Pernice et al , 2009; Sicari et al , 2015; Trombetta et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using histological analysis showed damage to the cuticle and gastrointestinal tract of nematodes in fish exposed to the EO of Thymus vulgaris (Giarratana et al, 2014) and Rlimonene (Giarratana et al, 2015), and to the EO of Cymbopogon sp. (Justino and Barros, 2008) and geraniol, citronellol, citral, carvacrol and cuminaldehyde (Hierro et al, 2004).…”
Section: In Vitro Activity Of Essential Oils On Fish Parasitesmentioning
confidence: 99%
“…Most of the in vitro studies on the effects of EOs or their compounds have been directed to A. simplex (Valero et al, 2015), a nematode that can cause zoonosis in humans (Hierro et al, 2004;Romero et al, 2014;Giarratana et al, 2015;Valero et al, 2015;Pérez et al, 2016), along with monogeneans (Tab. 2), which are helminths ectoparasites that cause great economic losses in fish farming due to epizootics (Steverding et al, 2005;Soler-Jiménez et al, 2017).…”
Section: In Vitro Activity Of Essential Oils On Fish Parasitesmentioning
confidence: 99%